Cacería ritual y sacrificios huicholes: entre depredación y alianza, intercambio e identificación - Johannes Neurath (Journal de la Société des Américanistes)
Ritual hunt and sacrifice among the Huichols: between predation and alliance, exchange and identification. This article intents to be a contribution to the ongoing debate whether « sacrifice » is still to be considered a useful analytical category or not. Parting from the heterogeneity of Huichol sacrificial practices, I’ll analyze the articulation between them. In my book Las fiestas de la Casa Grande (2002a), I underscored the dualism of sacrifice and self-sacrifice. Now I want to show how the whole spectrum of Huichol sacrificial practices can be found in every one of the rituals. In the case of the ritual sacrifice of domestic animals, I’ll analyze the articulation of exchange relations, « rebounding violence », and the sacrifier’s identification with his victim. Ritual deer hunt is interpreted as a voluntary self-sacrifice of the prey, as well as in terms of ritual condensation, defined, in this case, as the simultaneous existence of relations of predation and alliance.